Etika Komunikasi Netizen di Media Sosial pada Akun TikTok @Chikakiku Dalam Perspektif Islam - Rikeu Ainul Fadilah (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Currently, technological advances are developing rapidly, Indonesia is in the lowest rank in Southeast Asia according to data from the Digital Civility Index. Even though the majority of Indonesian people are Muslims. As for the presence of public figures who are the subject of discussion among netizens, Indonesian netizens should be able to apply communication ethics according to Islamic teachings. This study aims to determine the communication ethics of netizens on social media TikTok @Chikakiku from an Islamic perspective. This type of research is qualitative with descriptive analytical methods and data collection methods through observation, documentation, and interviews. Using the theory of Islamic communication principles. The results of this study indicate that the communication ethics of netizens on the TikTok account @Chikakiku have implemented Qaulan Kariman and Qaulan Ma'rufan with evidence of positive praise and support for Chika. There is also the ethics of netizens that are not in accordance with Qaulan Kariman and Qaulan Ma'rufan, namely comments that are blasphemous or put down. So netizens need to be wiser in using social media in positive and useful ways. Abstrak. Saat ini kemajuan teknologi berkembang pesat, Indonesia berada di urutan terbawah se-Asia Tenggara yang paling tidak sopan menurut data dari Digital Civility Index. Padahal mayoritas masyarakat Indonesia adalah beragama Islam. Adapun hadirnya public figure yang menjadi bahan perbincangan netizen yang seharusnya netizen Indonesia mampu menerapkan etika komunikasi sesuai ajaran Islam. Penelitian ini bertujuan untuk mengetahui etika komunikasi netizen di media sosial TikTok @Chikakiku dalam perspektif Islam. Jenis penelitiannya kualitatif dengan metode deskriptif analitis serta metode pengumpulan datanya melalui observasi, dokumentasi, dan wawancara. Menggunakan teori prinsip komunikasi Islam. Hasil penelitian ini menunjukkan bahwa etika komunikasi netizen pada akun TikTok @Chikakiku ada yang sudah menerapkan Qaulan Kariman dan Qaulan Ma'rufan dengan dibuktikan adanya pujian dan dukungan positif terhadap Chika. Ada pula etika netizen yang tidak sesuai dengan Qaulan Kariman dan Qaulan Ma'rufan yaitu adanya komentar yang menghujat atau menjatuhkan. Sehingga netizen perlu lebih bijak dalam menggunakan media sosial dengan hal positif dan bermanfaat.